Microbiology - Tortora, Gerard J. (Benjamin-Cummings Pub Co., 1995)
This edition continues to offer a balance of general and medical coverage of allied health microbiology. The text also combines accessibility and scientific accuracy, microbiology fundamentals and applications. Features include: updated and revised coverage of biotechnology, DNA, HIV and immunology; numerous critical thinking and clinical applications questions; and appendices including a pronunciation guide, a classification guide and further reading. This work is intended for biology, nursing and food science students studying introductory microbiology